Tajribi, Burhani and Bayani Abd Al-Jabiri Epistemology and Implementation in Islamic Education Philosophy Studies - Erni Haryanti; Nanat Fatah Natsir; Miftah Falah Udwi Syarfiah; Zahra Nur Azizah; Taufik Agung Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper describes the epistemology of bayani, tajribi and burhani in AlJabiri's thinking. Bayani is a thinking methodology model based on text. Whereas burhani is a methodology of the basis of logical chaos. For al-Jabiri the burhani epistemology must be an epistemology worthy of being applied in society to reduce the habit of romanticism that seeks knowledge through illuminative.